NILAI ESTETIKA TRADISI OMED-OMEDAN DI BANJAR KAJA, KELURAHAN SESETAN, KECAMATAN DENPASAR SELATAN - Anak Agung Raka Asmariani; Mery Ambarnuari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Abstract The omed-omedan tradition is a tradition of ancient heritage, passed down and performed by generations of Banjar Kaja Sesetan residents. Omed-Oedan is an entrenched tradition in accordance with the times while staying true to the prevailing norms. The uniqueness of the omed-omedan tradition attracts the attention of foreign tourists, turning it into an icon of Denpasar City. More than just a tradition, Omed-omedan contains aesthetic values. The present study on the aesthetic values in the omed-omedan tradition is a qualitative research and the data in this study are qualitative data. The theory used herein is the theory of aesthetics. Based on the results of study, the omed-omedan tradition contains subjective, objective and Hinduism aesthetic values related with: 1). Satyam (Truth), 2). Siwam (Sanctity) and 3). Sundaram (Harmony). Key words: omed-omedan tradition, Aesthetics